THE PATTERN OF TOPIC CHANGE IN SINGAPOREAN AND INDONESIAN CONVERSATION - Putri Andalasia, Ulfa; Azwandi, Azwandi; Diani, Irma (Sriwijaya University Learning and Education International Conference, 2018)
Conversation as the result of social interactions. It was constructed by culture, context and language. These phenomena related to Ethnography, the analyze of structural and organizational in language and culture. These were drawing a pattern, this schema of patternin conversationwasunpredictable,it distributed based on thetopics which used by participants. The aims of this research were drawing pattern and analyzing the topics in conversation. Dataanalyzedthroughethnography methodology incommunication. Whether the result showed thatthe conditionswere quite differenttothe theory.Firstispattern oftopic change informalconversationquite differenttothepreviousstudy andtheory.Second was the topics used in formal conversation controlled by the dominant participant, there were affected by the social status and context. These results may affectedby thecontext and setting of the conversation.